Jaringan Keagamaan dan Strategi Politik Lokal: Mediasi Politik Nahdlatul Ulama - Ahmad Yuzki Arifian Nawafi (JOM, 2025)
This study examines how Nahdlatul Ulama (NU) functions as a religious network that mediates local political processes and public policy in Tulungagung Regency, East Java, following the 2024 regional election. While much scholarship treats NU either as a national religious organization or as an electoral vote bank, the post-election mediating role of NU at the local level remains understudied. Using a qualitative case-study design that draws on in-depth interviews with NU functionaries, official electoral and regional-regulation documents, and direct observation, the research analyses NU's role through the lenses of network governance, political brokerage, symbolic capital, and policy feedback. The findings show that NU operates as a cultural-political broker, converting religious symbolic capital into electoral legitimacy and then sustaining it through long-term policy advocacy. NU safeguarded its religious-education policy (the Madrasah Diniyah regional regulation), mediated social and infrastructure programs such as Rutilahu, strengthened community-based economic empowerment through cooperatives, NU-affiliated MSMEs, and BMT, and maintained fluid political communication with the local government. The study concludes that NU's continued political relevance hinges on its consistency in upholding organizational values amid the pressures of local political pragmatism.